Relationships of the sport and the life quality in the University of Debrecen - Nagy, Ágoston (Acta Agraria Debreceniensis, 2009)
In the sport- life of the University of Debrecen there has been a demand formulated on the making of a comprehensive, long-term development plan, which obviously incorporates all fields of sport. This document guides the way for people in the sport- life of the university how they could organise their activities connected with sport on a calculable, predictable level. Necessarily, the preliminary collection of professional informations has been a basic requirement for the establishment of this document. The program provides foreseeable instructions to the organisation of sport pursuits both for sport people in the university, and members of the sport spehere in a wider sense. It offers a cohesive solution for all kinds of tasks defined with the sport life, and also gives a guidance for the various ways of realisations of these challenges. Thus it can answer such questions as for example how the university can conduce the initation of conditions for the healthy living through spare time sporting, how it can participate in the financing of contest sport with the contributing project of reinforcement training and how the university can support the sport life of handicapped people. The project also contributes to the cultivation of the sport traditions of the university by bankrolling not only the official university sport life but also the leisure time sporting of the students. On the basis of rethinking the situation of sport at the university with its future possibilities the program paraphrases the tasks of the university in the sport life, the long term aims of university sport politics with its operative aims that should be performed and also the possible steps which lead to these purposes. The target of the project is to turn the University of Debrcen in every field into a “Sporting University”. It means, that beyond the development of quality sport and outstanding contest sport a much wider range of university people should be included in sporting in order to utilize all the advantages of sport. With this the physical culture could become not only a substantial form of spending our free time, but with getting one of our natural everyday activities it can also become our lifestyle. Sporting prominently contributes to both the university students’s and the whole society’s mental and physical wellfare, and it also helps to improve our helthstate on various fields of life: with its special functions it is a means for establishing a healthy nation, for promoting common relationships, for nourishing the economic activity of people and also for strengthening the national values and one’s self-esteem through providing equal opportunities. The prosperousity of contest sport at the university and the maintaining and protesing of its efficiency fortifies our selfregard, as it is able to hold appropriate sportsmen up as examples to both present and future universtity students, and also offers exacting ways of entertainment. Besides all these the advataged purpose of the project is to find and delibaretaly include those necessary mechanisms which are needed for the working of the sport market.